Literature Review: Outcomes Profile In Appendicitis Patients With Laparoscopic Appendectomy And Open Appendectomy - Nurul Hikma; Sulfikar Rusdam; Mesak Sule; Reeny Purnamasari; Erwin Syarifuddin (Sean Institute, 2024)
Acute appendicitis is an abdominal emergency condition that commonly occurs in individuals of all ages. Traditionally, open appendectomy has been the standard method for treating appendicitis. However, with the advent of laparoscopy, laparoscopic appendectomy is now a promising alternative with potentially significant benefits. This study aims to evaluate and compare the results of laparoscopic appendectomy and open appendectomy in the treatment of acute appendicitis. From an analysis of 16 articles published between 2020-2024, laparoscopic appendectomy showed significant advantages, including less severe postoperative pain, shorter length of stay, faster recovery, and lower risk of complications such as wound infection. Overall, laparoscopic appendectomy is a better option in the treatment of acute appendicitis compared with open appendectomy.